THE FLUCTUATION EFFECT OF ATMOSPHERIC AMMONIA (NH3) EXPOSURE AND MICROCLIMATE ON HEREFORD BULLS HEMATOCHEMICAL - Mushawwir, A.; Yong, Y.K.; Adriani, L.; Hernawan, E.; Kamil, K.A. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
Ten Hereford bulls housed indoors in individual tie stalls were used to explore the relationshipsatmospheric ammonia exposure and microclimate on beef cattle hematochemical, and to know effectand to prediction equations the atmospheric ammonia exposure and microclimate with varioushematochemical parameters. This study was conducted in Animal Station, Department of AgriculturalBiotechnology, Seoul National University (SNU), Seoul, South Korea, for 40 days during summer.Results of this study indicated that there were negative correlation between ammonia with temperatureand positive correlation between ammonia with humidity. There were significantly negative effect ofammonia on hematochemical, except neutrophyls and ratio of neutrophyls to lymphocytes.Simultaneous effect between ammonia, temperature and humidity, mainly effected on glucose,hexokinase, lymphocytes, neutrophyls, N:L Ratio, and lactate. Simultaneous effect between ammonia,temperature and humidity proved to be a good indicator for predicting the profile of glucose,hexokinase, lymphocytes, neutrophyls, N:L Ratio in the blood.